Pengembangan Aplikasi Backend Pembuatan Surat (E-Surat) Dinas Komunikasi, Informatika, Dan Statistik Provinsi Bali - Rudyarta, I Gede Indra (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 7 No 2 (2018): JELIKU Volume 7 No 2, 2018, 2018)
Dinas Komunikasi, Informatika dan Statistik Provinsi Bali is the Regional Organization (OPD) which has the task of resolving the problems of Information Technology (IT) within the Bali Provincial Government and all regions in the Province of Bali. Each agency in carrying out the task or work that has been planned must issue an assignment letter or SPT from the competent authorities in order to assign staff / staff to do a job. In addition to the SPT there is an additional letter namely SPPD, but in its manufacture and archiving it still uses manual methods. The purpose of the research is to make the application of E-Surat of the Dinas Komunikasi, Informatika dan Statistik Provinsi Bali  made using the SDLC method by using baliprov.go.id hosting and MySQL databases. Applications are expected to be able to help make mailing easily, quickly, and minimize existing errors and better letter archiving. So that with this application the performance of the employees of the Dinas Komunikasi, Informatika, Dan Statistik Provinsi Bali   can be more optimal.